2021
DOI: 10.1177/0021909620988747
|View full text |Cite
|
Sign up to set email alerts
|

Public Spaces and Concentrations of Child Labourers in Ibadan Municipality, Nigeria

Abstract: Against the background of the solution-defying incidence of child labourers in Nigerian cities, this study examined the relationship between public spaces and incidence of child labourers in Ibadan Municipality, Nigeria. Data were obtained through direct counting of child labourers and cursory observation of the physical and environmental compositions of their places of operation. The direct counting was conducted for seven days of the week in the morning, afternoon and evening within defined activity-nuclei p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…It is imperative to mention that, as in other Nigerian cities, street children tend to have interrelationship with urban physical environment in Ibadan. That is to say, while street children, due to waste generation and indiscriminate disposal of same, obstruction of traffic flow and creation of ugly urban scene, constitute environmental nuisance, they are equally attracted by certain urban social, economic and environmental characteristics which provide convenient abode or suitable locations for them to operate (Taiwo et al, 2021). The environmental impacts of street children are restricted to the ugly and unmanageability site of the spatial units, while the proclivity to engage in criminal and nefarious activities constitutes the social implications of street children in Nigerian cities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is imperative to mention that, as in other Nigerian cities, street children tend to have interrelationship with urban physical environment in Ibadan. That is to say, while street children, due to waste generation and indiscriminate disposal of same, obstruction of traffic flow and creation of ugly urban scene, constitute environmental nuisance, they are equally attracted by certain urban social, economic and environmental characteristics which provide convenient abode or suitable locations for them to operate (Taiwo et al, 2021). The environmental impacts of street children are restricted to the ugly and unmanageability site of the spatial units, while the proclivity to engage in criminal and nefarious activities constitutes the social implications of street children in Nigerian cities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The proliferation of child hawkers has been observed as a social menace and environmental nuisance plaguing Nigerian urban centres (Abisoye, 2013; Dada, 2013 Taiwo et al, 2021). The phenomenon is yet to receive meaningful attention other than unsustainable forceful evacuation approach adopted sometimes in cities such as Lagos, Port Harcourt and Abuja, among others, to get the children off the streets.…”
Section: Theoretical Perspective Of the Studymentioning
confidence: 99%
“… 4 , 5 The 2007 Nigeria Population Reference Bureau (PRB) estimated 15 million street children in the country with the majority as children on the street. 5 A 2021 publication reported 5026 child labourers from a 7-day headcount exercise of children on the streets of Ibadan, Nigeria. 5 The Volunteer Work Africa (VWA), in 2022, estimated 100 000 street children in Lagos, Nigeria, the majority of whom were on the street for reasons of parental poverty, separation or unemployment.…”
Section: Introductionmentioning
confidence: 99%
“… 5 A 2021 publication reported 5026 child labourers from a 7-day headcount exercise of children on the streets of Ibadan, Nigeria. 5 The Volunteer Work Africa (VWA), in 2022, estimated 100 000 street children in Lagos, Nigeria, the majority of whom were on the street for reasons of parental poverty, separation or unemployment. 6 Owobu and colleagues, in 2022, reported that 9 out of 10 000 adolescents in Edo State, Nigeria were street children with existing family ties.…”
Section: Introductionmentioning
confidence: 99%